ANALISIS KESALAHAN MENURUT MODEL KIAT BERDASARKAN MINAT BELAJAR SISWA PADA MATERI PROGRAM LINIER SISWA SMK PERPAJAKAN RIAU - Jefrizal Hasyim; Yenita Roza; Maimunah Maimunah (KALAMATIKA Jurnal Pendidikan Matematika, 2022)
KIAT categorizes three types of mistakes: conceptual, procedural, and technical errors. This study analyzes student errors in solving mathematical problems on linear programming material based on student learning interests. The subjects of this study were 15 Year 10 students of Taxation Vocational High School majoring in business and management taken based on learning interests. This study employed a descriptive method with tests and questionnaires as the instruments. The outcomes confirmed that students with high interest in learning made 13 mistakes, while 19 and 20 errors were for students with moderate and low interest in learning, respectively. Of all the errors, based on the student's interest in learning, conceptual and procedural errors were the most common errors (20 errors each). It can be concluded that the more positive students’ attitudes, the lower the errors they make, especially on conceptual errors.